Do Manufacturing Firms Benefit from Services FDI? – Evidence from Six New EU Member States - Jože Damijan; Črt Kostevc; Philipp Marek; Matija Rojec (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
This paper focuses on the effect of foreign presence in the services sector on the productivity growth of downstream customers in the manufacturing sector in six EU new member countries in the course of their accession to the European Union. For this purpose, the analysis combines firm-level information, data on economic structures and annual national input-output tables. The findings suggest that services FDI may enhance productivity of manufacturing firms in Central and Eastern European (CEE) countries through vertical forward spillovers, and thereby contribute to their competitiveness. The consideration of firm characteristics shows that the magnitude of spillover effects depends on size, ownership structure, and initial productivity level of downstream firms as well as on the diverging technological intensity across sector on the supply and demand side. The results suggest that services FDI foster productivity of domestic rather than foreign controlled firms in the host economy. For the period between 2003 and 2008, the findings suggest that the increasing share of services provided by foreign affiliates enhanced the productivity growth of domestic firms in manufacturing by 0.16%. Furthermore, the firms' absorptive capability and the size reduce the spillover effect of services FDI on the productivity of manufacturing firms. A sectoral distinction shows that firms at the end of the value chain experience a larger productivity growth through services FDI, whereas the aggregate positive effect seems to be driven by FDI in energy supply. This does not hold for science-based industries, which are spurred by foreign presence in knowledge-intensive business services.
urn:nbn:de:101:1-201505263220
Keywords: D24; F15; 330; production; cost; capital; total factor and multifactor productivity; capacity; economic integration